Analisis Strategi Positioning terhadap Pangsa Pasar: - Yuyu Yuniarsih (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This research was conducted with the aim of knowing the analysis of positioning strategies, namely the strategy of placing a positive brand in the minds of consumers with the advantages and uniqueness of the product and making continuous purchases. Successful positioning will have an impact on increasing product sales, and of course will affect the market share that will be controlled by the product. The research method used is a qualitative method with a SWOT analysis, namely measuring strengths and weaknesses which are internal strategies (IFAS) and measuring external strategies consisting of opportunities and threats (EFAS). The result of research on Teh Botol Sosro for EFAS 2.5 and IFAS 2.95, the internal potential of The Botol Sosro is greater than the external potential. The strategy used in this condition is to support an aggressive growth policy (Growth Oriented Strategy). Board market share for packaged tea both domestically and for global market share. By using an aggressive growth strategy, The Botol Sosro can increase product sales more and will regain market share that has been captured by its competitors.